ELF AWARENESS FOR TEACHER EDUCATION IN ITALY: ATTITUDES AND ACTIONS - Grazzi, Enrico; Lopriore, Lucilla (Estudos Linguísticos e Literários, 2020)
The spread of English as the world’s primary lingua franca (ELF) poses some challenging questions about the impact of ELF on English language teaching (ELT). The gap between the dominance of native-speaker oriented institutional curricula and the emergence of variable, context-bound forms of English in multilingual and multicultural communicative settings is plain to see, opening up an opportunity for researchers to explore new directions in which future studies might be heading in order to implement an ELF-aware pedagogic approach to English. The aim of this article is to analyse a selection of relevant data that have been collected through a teacher survey on the state of the art as regards ELT. The survey was administered in Italy (mainly at upper and lower secondary school level). In particular, the authors focus their attention on issues such as learners’ errors, standard and non-standard English models, teachers’ attitudes and beliefs, the use of authentic materials, the encouragement of learners’ creativity, learner assessment and evaluation. This study, part of an Italian national research project, has been carried out by one of the three teams constituting the study group, the one from Roma Tre University, whose main objective is to take into consideration the changing scenario of Global Englishes and open new paths to revisit teachers’, learners’ and publishers’ beliefs and offer possible perspectives about classroom practices, assessment and evaluation, and material development.